Barriers to Same‐Day Discharge of Total and Completion Thyroidectomy Patients. (23rd August 2013) - Rutledge, Jonathan W.; Siegel, Eric R.; Bodenner, Don; Stack, Brendan C.
Abstract : Objectives: Thyroid surgery has traditionally been performed as an inpatient procedure due to the risk of postoperative hematoma and hypocalcaemia, but it is evolving into a safe outpatient procedure in selected patients. However, there is little in the literature about which patients require prolonged observation after planned same day surgery. Methods: A retrospective chart review was performed on patients from 2005 to 2012. We analyzed patients who underwent total thyroidectomy, completion thyroidectomy, or revision total thyroidectomy who were kept overnight or longer at a tertiary care center. Results: Two hundred thirty‐one cases qualified and planned for same day surgery. Eighty‐six patients were not discharged (37%). Twenty‐three of 86 patients were admitted for parathyroid hormone (PTH) <10. Eighty‐three percent of patients admitted had drains placed at the time of surgery, and most had their drains removed postoperative day (POD) 1 prior to discharge. Twelve patients required conversion to inpatient (14%). Eighty‐two point six percent of overnight observation patients were discharged home POD 1, and 96.5% were discharged by POD 2. Only one patient required readmission for hypocalcemia after observation and discharge. Conclusions: Intraoperative PTH <10 was the most frequent factor (27%) precluding same day discharge followed by admission for social/financial/transportation reasons (23%), large dead space (14%), multiple medical comorbidities (13%), multiple surgical reasons (11%), stridor (6%), pain management (4%), and intractable nausea due to general anesthetic (2%). Hypocalcemia and postoperative bleeding still remain obstacles to outpatient thyroid surgery; however, the use of rapid PTH, calcium prophylaxis, and power instrumentation facilitates same day surgery. Experienced clinical decision making can effectively stratify which patients require prolonged observation.